Cogeneration and Bioelectricity Production in the Sugarcane Energy Sector - Feroni, Wilson José; Silva, Itamar Nunes; Ramos, Leandro Rigo; Souza, Ozeas dos Santos Silva; Feroni, Rita de Cassia; Faria, Rochkhudson Batista de; Alborghetti, Millena Rodrigues (Latin American Journal of Energy Research, 2025)
Biomass from sugarcane plays an important role in the Brazilian energy matrix, offering both scale and energy flexibility. In this context, the aim of the present study is to analyze the Brazilian sugar-energy sector, with emphasis on cogeneration and the production of bioelectricity from sugarcane. The methodology included gathering information from government agencies and sector associations, as well as related studies on the topic. The results show that the Brazilian sugar-energy sector has significant potential for bioelectricity generation, driven by several factors. Despite this, it faces challenges that require public policies, intersectoral cooperation and investments. In 2023, 20.97 TWh were exported to the National Interconnected System, a volume sufficient to supply approximately 4% of the country’s electricity consumption, in addition to avoiding the emission of about 4.3 million tons of CO₂. Bioelectricity generation for the grid was concentrated during the dry season, strengthening energy security and reducing dependence on hydropower
Keywords: Biomass; Bioelectricity; Sugar-energy sector; Cogeneration